2019
DOI: 10.5692/clinicalneurol.cn-001264
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal intranuclear inclusion disease with prolonged impaired consciousness and status epilepticus: a case report

Abstract: Neuronal intranuclear inclusion disease (NIID) is a neurodegenerative disease presenting with various manifestations including dementia, weakness, transient impaired consciousness, encephalitis-like episodes and also epileptic seizures. However, the nature of epileptic seizures, focal or generalized onset, remains unclear. A man at age 76 was admitted to a local hospital due to febrile impaired consciousness lasting several days. During the hospital stay, a generalized convulsion occurred, and afterward he rem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 11 publications
1
7
0
Order By: Relevance
“…Sone et al ., summarized 38 sporadic adult-onset NIID cases, aged 51–76 years, with dementia onset as the main symptoms (94.7%), followed by limb tremor, ataxia, abnormal behavior, disturbance of consciousness, and encephalitis-like seizures ( 8 , 9 ). Others reported NIID with Parkinson-like symptoms ( 10 ), abnormal emotional behavior ( 11 ), chronic headache ( 12 ), sensory disturbance ( 13 ), epileptic episodes ( 14 ), cardiomyopathy, constipation and gastroenteritis, bronchopneumonia and respiratory failure ( 15 ), and dysphagia ( 12 ). However, there were no reports of early autonomic symptoms such as hypotension, pallor, profuse sweating, and syncope in patients with NIID.…”
Section: Discussionmentioning
confidence: 99%
“…Sone et al ., summarized 38 sporadic adult-onset NIID cases, aged 51–76 years, with dementia onset as the main symptoms (94.7%), followed by limb tremor, ataxia, abnormal behavior, disturbance of consciousness, and encephalitis-like seizures ( 8 , 9 ). Others reported NIID with Parkinson-like symptoms ( 10 ), abnormal emotional behavior ( 11 ), chronic headache ( 12 ), sensory disturbance ( 13 ), epileptic episodes ( 14 ), cardiomyopathy, constipation and gastroenteritis, bronchopneumonia and respiratory failure ( 15 ), and dysphagia ( 12 ). However, there were no reports of early autonomic symptoms such as hypotension, pallor, profuse sweating, and syncope in patients with NIID.…”
Section: Discussionmentioning
confidence: 99%
“…Although progressive symptoms, such as cognitive impairment and parkinsonism, are key features of NIID as a neurodegenerative disease, episodic attacks are also found in some patients with NIID, such as encephalitis-like, vestibular migraine-like attacks, or MELAS-like or epileptic episodes ( Xiao et al, 2018 ; Yamanaka et al, 2019 ; Ishihara et al, 2020 ; Li et al, 2020b ; Ataka et al, 2021 ; Zhao et al, 2021 ).…”
Section: Clinical Symptoms Of Neuronal Intranuclear Inclusion Diseasementioning
confidence: 99%
“…Although progressive symptoms, such as cognitive impairment and parkinsonism, are key features of NIID as a neurodegenerative disease, episodic attacks are also found in some patients with NIID, such as encephalitis-like, vestibular migraine-like attacks, or MELAS-like or epileptic episodes (Xiao et al, 2018;Yamanaka et al, 2019;Ishihara et al, 2020;Li et al, 2020b;Ataka et al, 2021;. Han et al (2019) reported a 63-year-old male with NIID who had recurrent acute encephalopathy syndrome, including recurrent headaches, personality changes, and abnormal mental behavior for 3 years.…”
Section: Episodic Attacksmentioning
confidence: 99%
“…NIID may be familial or sporadic, juvenile-onset (even infantile-onset), or adult-onset. NIID mostly has a chronic course, but acute attacks of headaches[ 1 ], epilepsy[ 2 ], and stroke-like[ 3 ] onset have also been reported. Sone et al [ 4 ] divided adult-onset NIID into two groups.…”
Section: Introductionmentioning
confidence: 99%